Online Credit Transactions from the Perspective of Tafsir Al-Munir (Case Study on the Kredivo Application) - Seruni, Atika; Rahmawati, Putri; Khofifah, Nur; Sari, Ayun Ratna; Najwanuddin, Muhammad Wildan; Arif, Fikri Khoirul; Abu Fatah Kurniawan, Fadhilah (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
The development of information and communication technology has transformed various aspects of human life, including the financial sector. One of the innovations in the financial sector is the emergence of online credit services that provide convenience for the public to access loans. This study aims to analyze the practice of online credit on the Kredivo application from the perspective of Tafsir Al-Munir. This study uses a qualitative approach with descriptive-analytical methods. The data sources used are the book of Tafsir Al-Munir by Wahbah Zuhaili and other secondary sources. The results of the study indicate that from the perspective of Tafsir Al-Munir, the practice of online credit on the Kredivo application, which imposes interest if payment exceeds the specified period, can be categorized as a riba transaction that needs to be avoided. Therefore, Kredivo users must be careful not to get caught up in the practice of riba.